2018
DOI: 10.1128/jvi.00342-18
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-Remodeling Factor SPOC1 Acts as a Cellular Restriction Factor against Human Cytomegalovirus by Repressing the Major Immediate Early Promoter

Abstract: 23The cellular protein SPOC1 (survival time-associated PHD finger protein in ovarian cancer 24 1) acts as a regulator of chromatin structure and DNA damage response. It binds 25H3K4me2/3 containing chromatin and promotes DNA condensation by recruiting 26 corepressors such as KAP-1 and H3K9 methyltransferases. Previous studies identified 27 SPOC1 as a restriction factor against human adenovirus (HAdV) infection that is 28 antagonized by E1B-55K/E4orf6-dependent proteasomal degradation. Here, we 29 demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Another group found that GSK3β (but not GSK3α) inhibition reduced both replication and viral particle production of HCV but not hepatitis E virus in Huh7.5 cells [175]. Moreover, GSK3-mediated phosphorylation appears to be involved in the destabilization of PHD finger protein 13, a host factor that (amongst other functions) is involved in repressing HIV-1 [176] and human cytomegalovirus gene expression [177]. Direct GSK3α/β-dependent phosphorylation of the coronavirus (CoV) nucelocapsid (N) has been described to be of importance for viral expansion, since GSK3 inhibition reduces both CoV-N phosphorylation and CoV replication [178].…”
Section: Role Of Gsk3 During Viral Infectionsmentioning
confidence: 99%
“…Another group found that GSK3β (but not GSK3α) inhibition reduced both replication and viral particle production of HCV but not hepatitis E virus in Huh7.5 cells [175]. Moreover, GSK3-mediated phosphorylation appears to be involved in the destabilization of PHD finger protein 13, a host factor that (amongst other functions) is involved in repressing HIV-1 [176] and human cytomegalovirus gene expression [177]. Direct GSK3α/β-dependent phosphorylation of the coronavirus (CoV) nucelocapsid (N) has been described to be of importance for viral expansion, since GSK3 inhibition reduces both CoV-N phosphorylation and CoV replication [178].…”
Section: Role Of Gsk3 During Viral Infectionsmentioning
confidence: 99%
“…At later steps of infection, SPOC1 levels start to decline upon phosphorylation by the serine-threonine kinase glycogen synthase kinase 3β (GSK-3β) (Hofmann et al, 2017). However, contrary to HIV-1 infection, where Vpr has already been identified as the viral protein involved in SPOC1 degradation (Reichel et al, 2018), the mechanism of HCMV-mediated downregulation of SPOC1 still remains obscure.…”
Section: Spoc1mentioning
confidence: 99%
“…This approach could be added to the previously mentioned strategies to purge the HCMV latent reservoirs. Interestingly, survival time-associated PHD finger protein in ovarian cancer 1 (SPOC1), a recently identified restriction factor against HCMV, associates with the proximal enhancer region of the MIEP and promotes heterochromatin condensation possibly through the recruitment of corepressors that SPOC1 is known to interact with notably the previously mentioned KAP-1 and H3K9 methyltransferase [88]. On the other hand, Ets-2 repressor factor (ERF) is a cellular protein that physically interacts with the HCMV MIEP and functions as a transcriptional repressor of the latter by suppressing IE gene expression [89].…”
Section: Human Cytomegalovirus and Epigeneticsmentioning
confidence: 99%